PARAGANGLIOMA AND ANGIOEDEMA - Tavares-Bello, Rui (2014)
Paragangliomas or extra-adrenal pheochromocytomas are rare tumors that arise from chromaffin tissues and tend to occur either sporadically or in the context of complex genetic disorders. They are clinically heterogeneous in nature - symptoms deriving either from the secretory profile of the tumor or from the mass effect of the neoplasm. Dermatologic symptoms are quite seldom described in the literature and have been classified in acute or chronic. The case of a 40 YO Caucasian female that had been enduring for the last 2 years recurring self-limited episodes of angioedema, diarrhoea, chest pain, hypertension or hypotension, dyspnoea and anxiety is reported. Biochemical studies and further imagiologic work up and, later on, pathologic exam allowed to identify a paraganglioma that drained to the left renal artery. Upon surgery, during tumor manipulation, the patient developed an additional systemic crisis that required active life support. Recovery was regular, with a quick and sustained normalization of lab results as well as on the clinical side, with no further episode for the last 17 years.